ROLE OF STRETCHING EXERCISES IN THE MANAGEMENT OF CONSTIPATION IN SPASTIC CEREBRAL PALSY - Awan, Waqar Ahmed; Masood, Tahir (Journal of Ayub Medical College Abbottabad, 2016)
Background: Constipation is considered as one of the most common non-motor manifestations in cerebral palsy (CP). Along with other reasons, spasticity also contributes in developing constipation in CP, by decreasing mobility of trunk and lower extremities and abdominal viscera. Stretching exercises of upper extremities, trunk and lower extremities are routine management of spasticity in CP children. The objective of the study was to determine the role of stretching exercises in improving constipation symptoms in children with spastic cerebral palsy and to explore the association between spasticity and constipation among cerebral palsy children. Methods: Single-group Pretest-Posttest Design (Quasi Experimental Study Design). The study was conducted at Physiotherapy Department of National Institute of Rehabilitation Medicine (NIRM) Islamabad. Thirty spastic CP children - both male and female - with complaints of constipation were recruited through non-probability, convenience sampling. The mean age of the children was 7.55±1.33 years. Each child was assessed for defecation frequency (DF), constipation severity by constipation assessment scale (CAS) and level of spasticity by modified ash worth scale for spasticity (MASS) at baseline. Stretching exercises were performed for 30 seconds with five repetitions and at least once a day for six week, followed by positioning of patients in reflex inhibiting posture. Final data was collected using the same tools as done at the baseline. Paired samples t-test was used to analyse the rehabilitation-induced changes after 6 weeks. To determine association between spasticity and constipation Pearson product-moment correlation coefficient was used. The data was analysed through SPSS 20. Results: Significant changes, compared to the baseline scores, were observed after 6 weeks of stretching exercises in MASS (2.53±0.62 Vs 1.53±0.77), DF (2.43±0.67 Vs 3.70±1.02) and CAS (7.23±1.50 Vs 5.43±1.73) with p‰¤0.05. The results also showed significant correlation between changes in levels of spasticity and severity of constipation (r = 0.37; p=0.04). Finally, significant correlation was present between improvement in spasticity and defecation frequency (r =-0.39; p=0.02). Conclusion: Stretching exercises administered for the management of spasticity in CP can significantly improve the symptoms of constipation in such children. The results of the study showed that constipation is strongly associated with level of spasticity in CP children. Keywords: Cerebral palsy; Constipation; Physiotherapy; Spasticity; Stretching exercises